Silicon carbide nanowire-reinforced micro-Ag joint based on pinning effect for power electronics packaging - Mulan Li; Shijun Huang; Zehao Chen; Jingwen Liu; Longlong Yan; Cai-Fu Li (Materials & Design)
Low-temperature sintering Ag technology is a feasible approach employed in power electron devices. In this study, the influence of the different amounts (0, 0.03, 0.05, 0.07, 0.10, 0.20 wt%) of silicon carbide nanowires (SiC NWs) on the properties and microstructure of micro-Ag paste sintered at 250 °C without pressure has been investigated. The results exhibit that the bonding strength of the Ag-SiC joint reaches a maximum of 43.57 MPa after doping 0.07 wt% SiC NWs, with an increase of 13 % compared with pure Ag joint. This enhancement mechanism can be owed to the Orowan mechanism and the pinning effect of SiC NWs, which nail at grain boundaries that will restrain the dislocation motion of Ag grains. Meanwhile, the electrical resistivity of Ag-0.07SiC shows a minimum value of 5.20 μΩ cm, approximately 10.65 % lower than pure Ag joint. This is attributed to the well-sintered Ag network and the bridging effect of SiC NWs distributed in Ag particles. Thus, incorporating appropriate content of SiC NWs into micro-Ag paste can strengthen the mechanical performance and electrical conductivity of sintered Ag joint. It is hoped that this research could develop a new micro-Ag paste with outstanding properties that could be employed in high-power electronic devices.